Effect of icosahedral phase on the crystallographic texture and mechanical anisotropy of duplex structured Mg–Li alloys. (25th December 2015) - Xu, D.K.; Li, C.Q.; Wang, B.J.; Han, E.H.
Abstract: Through comparing the microstructure and mechanical properties of Mg–6%Li and Mg–6%Li–6%Zn–1.2%Y alloys, the difference in their mechanical anisotropy have been deeply investigated. Due to the formation of I-phase (Mg3 Zn6 Y, icosohedral structure), the volume fraction of β-Li phases formed in Mg–6%Li–6%Zn–1.2%Y alloy was two times higher than that in Mg–6%Li alloy even these two alloys having the same Li content. Texture analysis demonstrated that I-phase particle stimulated nucleation of recrystallization (PSN) and the formation of higher volume fraction of β-Li phases can remarkably weaken the basal texture of α-Mg phases, resulting in a very weak mechanical anisotropy. On the contrary, the basal texture of the α-Mg phases in Mg–6%Li alloy was quite strong and obvious mechanical anisotropy between differently oriented samples can be observed. Graphical abstract: Highlights: I-phase strengthened Mg–Li alloy has a weaker basal texture of α-Mg phases. I-phase strengthened Mg–Li alloy exhibits a weaker mechanical anisotropy.